1986
DOI: 10.1007/bf01748098
|View full text |Cite
|
Sign up to set email alerts
|

On the fcc → hcp transformation in a cobalt-base superalloy (Haynes alloy No. 25)

Abstract: It is known that the cobalt-based family of Multiphase alloys (Multiphase is a registered trademark of SPS Technologies, Inc.) derive their strength, in part, from cold working and that additional strengthening can be obtained by subsequent ageing heat treatments [1][2][3][4][5][6][7][8][9]. In the case of alloy MP35N ( 3 5 C o -3 5 N i -2 0 C r10Mo, in wt %), the strengthening associated with cold working is attributed to a face-centred cubic (fc c) -~ hexagonal close-packed (h c p) transformation and/or form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 6 publications
2
18
0
Order By: Relevance
“…This also has been reported that [26], formation of ε-HCP does not occur in nickel stabilized γ phase after heat treatment, but the material can undergo the martensite transformation during room-temperature plastic deformation. According to the results that obtained for hardness in this study, it is highly likely to form HCP phase in FCC matrix of L-605 alloy after cold rolling and heat treatment.…”
Section: Hardnesssupporting
confidence: 67%
“…This also has been reported that [26], formation of ε-HCP does not occur in nickel stabilized γ phase after heat treatment, but the material can undergo the martensite transformation during room-temperature plastic deformation. According to the results that obtained for hardness in this study, it is highly likely to form HCP phase in FCC matrix of L-605 alloy after cold rolling and heat treatment.…”
Section: Hardnesssupporting
confidence: 67%
“…Moreover, it has been reported [8,14,15] that in Co-Cr-Mo superalloys martensitic transformation after heat treatment of cold-worked alloys can occur so that an hcp phase can be formed in fcc matrix.…”
Section: Fig 3 Variations Of Hardness With Annealing Time For Variomentioning
confidence: 99%
“…Koizumi et al [8] and Tawancy et al [9] have reported, it is highly likely that the transformation of fcc to hcp happens in alloys with low stacking fault energy. According to these findings, there is a strong likelihood that the stacking faults on every {111} atomic planes of γ-fcc will be transformed to {0001} plane of the ε-hcp phase; by changing the stacking sequence on the {111} planes of fcc phase from …ABCABC… type to …ABAB… type related to {0001} planes of hcp phase.…”
Section: Introductionmentioning
confidence: 99%
“…[9] into Eq. [10] gives [11] Subsequently, n can be determined from Eq. [11]; e.g., for the hysteresis loop in Figure 7, n is equal to 0.1658.…”
Section: Total Plastic-strain-energy Density As a Criterion For Fmentioning
confidence: 99%
“…[6][7][8][9][10] The nominal chemical composition of ULTIMET alloy, developed by Haynes International, Inc., is shown in Table I. [11] It is typically used in the solution-annealed condition, and possesses high tensile strength combined with excellent impact toughness and ductility.…”
Section: Introductionmentioning
confidence: 99%